Penilaian Kualitas Visual Lanskap The Bay Villas Resort, Tanjung Lesung - Banten - Walidain, Intan Fadhilah Birrul; Budiyanti, Rully Besari; Yuslim, Silia (Jurnal Arsitektur Lansekap, 2021)
Visual quality assessment of The Bay Villas Resort, Tanjung Lesung Banten. The Bay Villas Resort is a recreational area located in Tanjung Lesung, Banten, and is equipped with facilities to stay overnight. The Bay Villas Resort has beautiful natural and visual resource potential. The beach is clean and beautiful, overlooking the Sunda Strait and leading to Mount Krakatau. The problem is that the existing visual potential has not been utilized optimally. This can be seen from the unavailability of facilities for outdoor activities that take advantage of this potential. This study uses qualitative methods with research instruments in the form of observation followed by visual potential assessment with assessment methods. Data analysis used interval classes which were then classified according to their visual quality. This study aims to identify the visual potential as the basis for the development of the landscape of The Bay Villas Resort according to the characteristics and visual quality. The results of the research in the form of landscape visual quality which are classified into high, medium, and low landscape visual qualities will be useful as a basis for the placement of facilities in further landscape development.